Evaluation of the Islamic Education Curriculum in Islamic Boarding Schools: Assessing the Impact on the Quality of Learning and Curriculum Management - Moh Wardi; Ismail Ismail; Supandi Supandi; Hodairiyah Hodairiyah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: Islamic religious education (PAI) in Indonesia plays a pivotal role in nurturing the character, morality, and spirituality of the younger generation. Among the key institutions delivering PAI are Islamic boarding schools (pesantren), which integrate religious and general education within a unique cultural and educational framework. This study aims to critically analyze the implementation of the Islamic education curriculum in pesantren and to assess its impact on educational quality and relevance in a rapidly changing societal context. Methodology: Adopting a qualitative library research approach, this study systematically examines scholarly literature, policy documents, and prior research to explore curriculum practices in pesantren. The focus is on understanding both traditional and modern models of curriculum integration and the challenges faced in adapting Islamic education to contemporary educational standards. Main Findings: The study reveals that traditional pesantren, emphasizing classical religious sciences, often encounter difficulties integrating competency-based curriculum reforms demanded by modern education systems. Conversely, progressive pesantren that adopt competency-based frameworks exhibit significant improvements in educational quality, particularly in practical skills aligned with societal and workforce needs. However, the transition remains uneven and faces structural challenges. Novelty/Originality of this Study: This research offers a novel perspective by highlighting the tension between maintaining religious authenticity and pursuing educational modernization in pesantren. It proposes a strategic model for curriculum transformation supported by government policy, teacher capacity building, and infrastructural enhancement. This study contributes to reimagining Islamic boarding schools as dynamic institutions capable of preserving religious values while equipping students for global challenges.